Contact eczema - Szczepaniak, Elżbieta; Prokop, Janusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Contact eczema is a one of the most frequent skin diseases. Depends on etiopathogenesis it can be divided into allergic and non-allergic, so called: irritation eczema. Compounds, which release non-allergic skin changes, are compounds originally irritating. The basis of the contact eczema is IV immunologic mechanism, so called: retarded answer. Most common contact allergens are: chromium, nickel, cobalt, ingredients of gum, paragroup’s compounds, epoxide resin, external drugs, formalin, cosmetic compounds.